2016
DOI: 10.1002/14651858.cd007587.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the prevention of tension-type headache

Abstract: Background Acupuncture is often used for prevention of tension-type headache but its effectiveness is still controversial. This is an update of our Cochrane review originally published in Issue 1, 2009 of The Cochrane Library. Objectives To investigate whether acupuncture is a) more effective than no prophylactic treatment/routine care only; b) more effective than ‘sham’ (placebo) acupuncture; and c) as effective as other interventions in reducing headache frequency in adults with episodic or chronic tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 79 publications
5
141
1
6
Order By: Relevance
“…A systematic review (12 RCTs, 2349 patients) reported a ≥50% reduction in headache frequency in 48% and 45% of patients receiving acupuncture compared with nonacupuncture controls (4% and 19%) and in 51% of those receiving acupuncture compared with 43% of sham acupuncture controls (moderate quality evidence). 17 …”
Section: Preventionmentioning
confidence: 99%
“…A systematic review (12 RCTs, 2349 patients) reported a ≥50% reduction in headache frequency in 48% and 45% of patients receiving acupuncture compared with nonacupuncture controls (4% and 19%) and in 51% of those receiving acupuncture compared with 43% of sham acupuncture controls (moderate quality evidence). 17 …”
Section: Preventionmentioning
confidence: 99%
“…The published literature pertaining to the effectiveness of acupuncture for tension‐type headache was summarized in a Cochrane Database systematic review published in 2016 . This review included 12 trials representing 2349 patients with tension‐type headache who participated in RCTs that compared acupuncture to routine care only (2 trials), sham acupuncture (7 trials), or physiotherapy, massage, or relaxation (4 trials).…”
Section: Acupuncture For Tension‐type Headachementioning
confidence: 99%
“…2,3 Between 1990 and 2013, the burden of migraine, medication overuse headache, and TTH, defined in terms of years lived with a disability (YLDs), increased by 46.1%, 45.5%, and 120.2%, respectively. [11][12][13][14][15] Behavioral approaches vary somewhat, both in descriptive terms and specific aims, but a common thread involves changing maladaptive behaviors and ways of thinking that contribute to headache-related burden and pain. 4 Current first-line treatments for primary headaches include medications for acute management, such as triptans and nonsteroidal anti-inflammatory drugs, and prophylactic drugs with a variety of options, including oral medications such as antidepressants, anti-epileptics, and b-blockers, and local injections such as onabotulinumtoxinA.…”
Section: Introductionmentioning
confidence: 99%